Classrooms Through the Eyes of High Achievers: Gender Differences in Situational Experiences Based on the DIAMONDS Framework - Ketscher, Lukas; Stoeger, Heidrun; Ziegler, Albert (Journal of Advanced Academics, 2025)
The persistent underrepresentation of girls among top performers in STEM has long been a concern in talent development research. Recent studies, however, suggest that this gender gap may be narrowing. This study investigates whether gender and academic achievement shape how students perceive STEM classroom situations, using the DIAMONDS framework, a taxonomy of psychological meaningful situational characteristics (e.g., Duty, Intellect). Data were analyzed from 1,024 German eighth-grade students. In contrast to historical trends, our sample showed equal representation of boys and girls among the top 10% of STEM achievers. While no interaction effects were found between gender and achievement, consistent main effects emerged: girls reported higher levels of Duty and Intellect, but also greater Negativity and Deception; boys perceived STEM lessons more positively overall. High-achieving students, regardless of gender, experienced STEM situations more positively than their lower-achieving peers. These findings in our context suggest that gender disparities in top STEM performance may diminish, but that gender differences in classroom perception persist.
CRIS-Team Scopus Importer:2025-12-05
Keywords: DIAMONDS; gender differences; high achievement; situational perception; STEM